Studying the absorption of light rays by using some of Zinc alloys - Jbeli, Haisam; Molhem, Jehad; Daher , Taghred (Latakia University Journal -Basic Sciences Series, 2018)
In this research we have studied the absorbance of some zinc alloys. These alloys were manufactured in the local market, and these alloys can be used as absorber plate in the manufacture of solar collectors. We conducted this study in the laboratory, first (using tow light sources, 100W and 30 W), and Second in the external medium using direct solar radiation. Our research provides important information that could be used in improving the efficiency of solar collectors using absorbent surfaces that has a higher absorbency. We have also studied the relationship between the absorbance and the atomic number of the studied alloys. This study showed that the absorbed energy by these metals increase with their atomic laboratory number Z.